Hubungan Antara Public Relations dan Citra Merek: (Studi Kasus Pada Merek Terkenal di Indonesia) - Vivi Anggriani; Adela Lora Tri Andini; Melani Putri Dewitasari; Madinatul Munawaroh; M. Angga Maulana; M. Inwan Rosyadi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research examines the relationship between public relations (PR) strategies and brand image formation in leading companies in Indonesia. Using a case study approach, this research analyzes how PR activities contribute to the formation, maintenance, and recovery of brand image. The results show a positive correlation between the implementation of effective PR strategies and brand image enhancement. This study also identifies PR best practices applied by successful brands in Indonesia in building positive perceptions among consumers and stakeholders. The findings provide valuable insights for PR and marketing practitioners in optimizing communication strategies to strengthen brand image in the competitive digital era.